Genetic and environmental effects on production of dairy goats under semi-intensive tropical conditions - Campos-Alfaro, Jorge A.; Vargas-Leitón, Bernardo; Alpízar-Naranjo, Andrés H.; Padilla-Fallas, José E.; Camacho-Cascante, M. Isabel (Agronomía Mesoamericana, 2025)
Introduction. The study of factors affecting the productive performance of dairy goats under tropical conditions is essential for optimal resource utilization. Objective. To quantify the impact of genetic and environmental factors affecting the productive performance of dairy goats under semi-intensive tropical conditions. Materials and methods. The research was conducted at the Finca Experimental Santa Lucía of the Universidad Nacional, Heredia, Costa Rica. The experimental period spanned from January 2007 to December 2023. A total of 15,686 daily milk yield records were analyzed from 191 dairy goats of Saanen (S) and Saanen•Toggenburg (S•T) breed types. A generalized linear mixed model was used to evaluate the effect of various predictor variables on daily milk yield, and standard lactation curves were fitted for different genetic and environmental conditions using the Wood function. Results. Highly significant effects (p < 0.001) were determined for parity number, year of kidding, lactation week, buck category, number of offspring, season, and month of kidding on milk yield. For primiparous goats of S and S•T breeds kidding in the rainy season, peak daily milk yields of 2.46 and 2.54 kg were estimated, reached at weeks 6.4 and 5.9, with persistencies at the end of lactation of 86 % and 84 %, respectively. Conclusions. Multiparous status and access to feed with higher nutritional content during the rainy season were factors associated with higher milk yield. Lactation curves revealed different patterns in milk production between primiparous and multiparous goats, as well as among different kidding seasons and breed types. The study provides valuable information for commercial validation and optimization of lactating goat management under semi-intensive tropical conditions.